Adverse effects of laxatives: update. (April 2017) - Anton, Christopher; Crawford, Colin
Abstract : Summary: Laxatives are generally well tolerated and adverse effects mild or moderate, although rarely adverse effects can be fatal. Several laxatives have recently been licensed for intractable constipation not relieved by simple laxatives, opioid-induced constipation, and irritable bowel syndrome with constipation. Like the older laxatives, the new laxatives usually cause only mild adverse effects, although some serious effects have been reported.